The Effects of Motivation, Organizational Citizenship Behavior, and Transformational Leadership on The Performance of Gen Z Employees in Bandung - Raihan Andhika Pratama; Didin Kristinawati (Cakrawala Repositori IMWI)
Employee performance is a vital determinant in attaining organizational objectives, influenced by factors such as job motivation, Organizational Citizenship Behavior (OCB), and Transformational Leadership. This study intends to investigate the influence of three factors on the performance of Generation Z employees in Bandung City, where this cohort represents a substantial portion of the workforce. Generation Z, having been raised in the digital age, exhibits unique traits relative to earlier generations, resulting in heightened expectations regarding job flexibility and the significance of their positions. Consequently, comprehending the elements that affect their performance is essential for firms aiming to improve the efficiency and productivity of this emerging workforce. The principal objective of this study is to examine the impact of work motivation, organizational citizenship behavior, and Transformational leadership on the performance of Generation Z employees in Bandung City. The study aims to determine if these three variables significantly affect employee performance, both independently and in combination. By comprehending the interconnections among these characteristics, firms can formulate more precise management strategies to improve Gen Z employee performance. This research seeks to address the paucity of studies regarding the impact of these characteristics on the Gen Z demographic, a topic with few investigation. This study utilizes a quantitative methodology including an explanatory research design. It use multiple linear regression analysis to investigate the impact of independent variables (work motivation, organizational citizenship behavior, and Transformational leadership) on the dependent variable (employee performance). Data will be gathered via surveys administered to 170 respondents, specifically Gen Z employees in Bandung City. Statistical tools, such as SPSS, will be utilized for data analysis, and hypothesis testing will be executed both partially and concurrently. This strategy seeks to elucidate the elements affecting the performance of Gen Z employees in the workplace.